2019
DOI: 10.2967/jnumed.119.230979
|View full text |Cite
|
Sign up to set email alerts
|

High Availability of the α7-Nicotinic Acetylcholine Receptor in Brains of Individuals with Mild Cognitive Impairment: A Pilot Study Using 18F-ASEM PET

Abstract: Emerging evidence supports a hypothesized role for the α7-nicotinic acetylcholine receptor (α7-nAChR) in the pathophysiology of Alzheimer's disease. 18 F-ASEM (3-(1,4-diazabicyclo[3.2.2]nonan-4-yl)-6-18 F-fluorodibenzo[b,d]thiophene 5,5-dioxide) is a radioligand for estimating the availability of α7-nAChR in the brain in vivo with PET. Methods: In this cross-sectional study, 14 patients with mild cognitive impairment (MCI), a prodromal stage to dementia, and 17 cognitively intact, elderly controls completed 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…AD (Coughlin et al, 2018(Coughlin et al, , 2019. A preliminary imaging study of M4 mAChR in AD revealed reduced uptake of [ 11 C]MK-6884 primarily in the parietotemporal cortex in a pattern consistent with clinical symptom presentations and FDG hypometabolism (Masdeu et al, 2020).…”
Section: Imaging Research Findings and Clinical Relevancementioning
confidence: 87%
See 1 more Smart Citation
“…AD (Coughlin et al, 2018(Coughlin et al, , 2019. A preliminary imaging study of M4 mAChR in AD revealed reduced uptake of [ 11 C]MK-6884 primarily in the parietotemporal cortex in a pattern consistent with clinical symptom presentations and FDG hypometabolism (Masdeu et al, 2020).…”
Section: Imaging Research Findings and Clinical Relevancementioning
confidence: 87%
“…Episodic memory, working memory and executive functions are well-correlated with impairment of α 4 β 2 nAChR in the corresponding cortices. Initial imaging studies with the α 7 nAChR selective radioligand [ 18 F]ASEM in healthy controls and MCI subjects indicated elevation of this receptor subtype with healthy aging, and in MCI, in a direction opposite of that for α 4 β 2 nAChR in AD (Coughlin et al, 2018 , 2019 ). A preliminary imaging study of M4 mAChR in AD revealed reduced uptake of [ 11 C]MK-6884 primarily in the parietotemporal cortex in a pattern consistent with clinical symptom presentations and FDG hypometabolism (Masdeu et al, 2020 ).…”
Section: Pet Tracers For Imaging Targets In the Cholinergic Systemmentioning
confidence: 99%
“…A comparative PET study comparing [ 18 F]ASEM and [ 18 F]DBT-10 indicated that [ 18 F]ASEM harbored better brain uptake and kinetic behavior in non-human primates ( Hillmer et al, 2017 ). [ 18 F]ASEM imaging was reported in patients with mild cognitive impairment ( Coughlin et al, 2020 ), psychosis ( Coughlin J. et al, 2018 ), schizophrenia ( Wong et al, 2018 ), and in healthy aging ( Coughlin J. M. et al, 2018 ). Coughlin et al (2020) showed an increased cerebral [ 18 F]ASEM measure of α7 nAChR in patients with mild cognitive impairment compared to healthy controls.…”
Section: Synaptic Neurotransmitter Receptorsmentioning
confidence: 99%
“…[ 18 F]ASEM imaging was reported in patients with mild cognitive impairment ( Coughlin et al, 2020 ), psychosis ( Coughlin J. et al, 2018 ), schizophrenia ( Wong et al, 2018 ), and in healthy aging ( Coughlin J. M. et al, 2018 ). Coughlin et al (2020) showed an increased cerebral [ 18 F]ASEM measure of α7 nAChR in patients with mild cognitive impairment compared to healthy controls.…”
Section: Synaptic Neurotransmitter Receptorsmentioning
confidence: 99%
“…Further, to the author's knowledge, no prospective, blinded studies have been conducted evaluating [ 18 F]ASEM PET's accuracy in identifying patients with psychosis over healthy controls. Additionally, recent studies suggest that levels of the α7-nAChR are abnormal in individuals with mild cognitive impairment [46] and change naturally with aging [47], both of which would confound the tracer's ability to identify individuals with psychosis over other neuropathological illnesses. Used alongside professional judgement and symptomatic evaluation, however, [ 18 F]ASEM PET may possess utility as a diagnostic marker of psychosis.…”
Section: α7-nachr Receptormentioning
confidence: 99%